Current interventional coronary applications of excimer laser. (July 2013) - Fracassi, Francesco; Roberto, Marco; Niccoli, Giampaolo
Excimer laser utilization as an adjunctive device for percutaneous coronary intervention has increased in the last few years. Many technical advancements have led to better results in terms of efficacy and safety with a low complication rate. In particular, excimer laser for thrombus-containing lesions is able to achieve rapid thrombus removal and plaque debulking along with subsequent facilitation of stent angioplasty and a low rate of microvascular obstruction. Other indications for laser angioplasty embrace in-stent restenosis, chronic total occlusions, saphenous vein graft lesions and new potential applications, such as stent expansion optimization and bifurcation lesions. As for other medical devices, however, excimer laser should be tested in future randomized studies against current standard of therapy in order to better define its role for each of the indications summarized above.